Dispossession Anthropological Perspectives on Russia's War Against Ukraine - Wanner, Catherine (Anthropology of Now, 2024)
This volume examines Russia's war on Ukraine. Scholars who have lived through the Russian invasion or who have conducted ethnographic research in the region for decades provide timely analysis of a war that will leave a lasting mark on the twenty-first century. Using the concept of dispossession, this volume showcases some of the novel ways violence operates in the Russian-Ukrainian war and the multiple means by which civilians, within the conflict zone and beyond, have become active participants in the war effort. Anthropological perspectives on war provide on-the-ground insight, historically informed analysis, and theoretical engagement to depict the experiences of dispossession by war and the motivations that drive the responses of the dispossessed. Such perspectives humanize the victims even as they depict the very inhumanity of war. Dispossession is geared towards upper-level undergraduate and graduate students, scholars, and the general reader who seeks to have a deeper understanding of the Russian-Ukrainian war as it continues to impact geopolitics more broadly.